The role of hopelessness and gratitude in the association between brooding and Chinese college students' suicidal ideation: a moderated mediation model. Issue 6 (3rd July 2021) - Liu, Yu; Yang, Yang; Jia, Xuji; Wang, Chenxu; Mo, Juanchan; Jiang, Zhehao; Lin, Lin
ABSTRACT: Based on the cognitive model of suicide and broaden-and-build theory of gratitude, this study constructed a moderated mediation model to examine whether hopelessness mediated the relationship between brooding and Chinese college students' suicidal ideation and whether this mediating process was moderated by gratitude, from the positive psychology perspective. A total of 1191 college students were investigated using four scales. The results were as follows: (1) Brooding significantly contributed to suicidal ideation; (2) Hopelessness played a mediating role in the relationship between brooding and suicidal ideation; and (3) Gratitude moderated the mediated path through hopelessness, such that this mediating effect was only significant in individuals with low gratitude. This study may shed light on how brooding influences Chinese college students' suicidal ideation theoretically and on their prevention practically.